INVESTIGATION OF EARTHQUAKE-INDUCED LANDSLIDE ALONG WAY RATAI ROAD, TELUK PANDAN, LAMPUNG, INDONESIA USING ON-GROUND SHEAR STRAIN AND SOFT LAYER THICKNESS ANALYSIS - Elvina Damayanti Elvina; Ikah Ning Prasetiowati Permanasari; Vico Luthfi Ipmawan (Universitas Mataram, 2026)
Seismic shaking is a primary trigger of landslides in tectonically active regions. In the Teluk Pandan area, Lampung, Indonesia, earthquake hazards are associated with the nearby megathrust southwest of Lampung Province, the Great Sumatran Fault—particularly the Semangko segment—and other active regional faults. This study aims to investigate the extent to which earthquakes contribute the occurrence of landslides using ground shear strain (GSS) value and the thickness of soft soil layers along Way Ratai Road, the main route to a tourist destination. GSS values range from to , all below the 10⁻⁴ threshold, indicating predominantly elastic soil behaviour with no permanent deformation under current seismic loading conditions. Despite this, potential vulnerability remains, particularly under scenario earthquakes originating from the nearby Lampung-Panjang Fault ( 12 km). Soft soil thickness varies from 0.2 m to 178 m, with critical locations (T25, T28, and T43) exhibiting very thick deposits (149–178 m), which can significantly amplify seismic waves. This amplification effect, combined with high annual rainfall ( 3000 mm/year), increases the likelihood of slope instability and landslide occurrence. The results demonstrate that low GSS values alone may not fully represent landslide hazard. Therefore, integrating GSS with subsurface soil conditions is essential for more reliable and conservative landslide susceptibility assessment in earthquake-prone areas.